Les ATSEM, les activités manuelles et la raison graphique - Fabienne Montmasson-Michel (Recherches en Éducation)
Service women in French nursery schools (now ATSEM) have acquired an indispensable place among the teachers. While they were contained in the margins of educational activities, they entered classrooms in the last decades of the twentieth century and acquired pedagogical skills. During nursery school’s development in the second part of the twentieth century, language has become a priority. Young children are expected to be introduced into the written culture demanded by long schooling. Since then, a social division of pedagogical work has emerged: teachers become responsible to the most legitimate fields, while ATSEM achieve material preparation, classification of work and conduct "manual activities". An ethnographic research studying language socialization of young children grasps their pedagogical work. It shows its contribution to initiate children in the written culture. ATSEM order bodies and objects. They accompany bodily children while objectifying in their words graphic and scriptural concepts. They thus convey a useful school culture, well present in the classrooms. However, this way to do is delegitimized by the prescription field, favoring reflexive processes and presupposing autonomy already there.